Effects of Cognitive Reframing and Self-Management Techniques on Dependent Personality Behaviour among Senior Secondary School Students in Suleja Education Zone, Niger State, Nigeria (Journal of Guidance and Counselling Studies, 2023)
This study examined the effects of cognitive reframing and self-management counselling techniques on dependent personality behaviour among senior secondary school students in Suleja education zone of Niger State, Nigeria. One objective guided the study which involve to determine the differential effect of self-management technique on dependent personality behaviour among senior secondary school students in Suleja education zone, Niger State. Also, one research questions was raised and answered, one hypothesis was formulated and tested at 0.05 level of significance, all in line with the objective of the study. Quasi-experimental design involving pre-test post-test experimental group design was adopted for the study. Population of the study comprised of all the senior secondary school students identified with dependent personality behaviour in Suleja education zone of Niger State. Total number of twenty five (25) students were identified in two selected schools in Suleja education zone of Niger State, and twenty (20) of them were purposively selected and used as a sample in this study. Dependent Personality Screening Scale was used for the identification of the students with dependent personality behaviour, and Dependent Personality Behaviour Questionnaire was used for the collection of pre-test and post-test data for the study. Data collected was analyzed using paired and independent sample t-test at 0.05 alpha level of significance. The findings revealed that there is no significant difference in the effectiveness of cognitive reframing and self-management counselling techniques on dependent personality behaviour among senior secondary school students in Suleja education zone, Niger State (p = 0.311). Based on these findings, it was recommended that school guidance counsellors, school psychologists, and teachers should be encouraged to use both cognitive-reframing and self-management counselling techniques in handling dependent personality behaviour among senior secondary school students, because both the techniques proved similar efficient in reducing dependent personality behaviour among senior secondary school students.
Keywords: Dependent; Personality; Behaviour; Cognitive; reframing and Self-Management